Multicultural and multidisciplinary courses in communication online – why on earth? - Kivimäki, Sanna (Žurnalistikos tyrimai, 2009)
In my article, I reflect the pedagogical challenges and potentials of internationalization, multiculturalism, multidisciplinary and the usage of ICT in higher education. I focus on online courses arranged by the Finnish University Network for Communication Sciences, which has cooperated in arranging multicultural and multidisciplinary online courses for several years. I start by reviewing several recent transition lines in university cultures. Next, I introduce the network’s courses in more detail and discuss the challenges and possibilities of this kind of education. Finally, I argue that despite all the major challenges of multicultural and multidisciplinary online courses, students can learn not merely interesting and current topics but also useful skills needed in both academic and working life. For instance, the ability to meet, recognize and negotiate differences is undoubtedly an essential competence in the globalized world. Keywords: online courses, higher education, networks, cooperation, multiculturalism, multidisciplinarity. p>